Development of a Case Study-Based Digital Book to Enhance Learning in Office Management Education - Durinda Puspasari; Durinta Puspasari; Ruri Nurul Aeni Wulandari; Lifa Farida Panduwinata; Andy Parsetyo Wati (International Journal of Studies in International Education, 2025)
This study focuses on the development of a case study–based digital book aimed at improving learning quality in Office Management education, where students are required to master both conceptual understanding and practical decision-making skills. Despite the increasing use of digital learning resources in higher education, existing instructional materials often lack contextual integration between theory and real workplace scenarios, resulting in limited student engagement and insufficient opportunities for problem-based learning. To address this issue, the present research aims to design and develop an interactive digital book enriched with authentic case studies that align with course learning outcomes. The study employed a Research and Development approach using the 4-D model Define, Design, and Develop to produce learning materials validated by experts and tested through limited trials. The results show that the digital book achieved high feasibility, with an average expert validation score of 87.33%, while student responses reached 93.87%, indicating strong acceptance, improved motivation, and enhanced perceived understanding. The synthesis of these findings demonstrates that embedding case-based learning elements into digital book formats can effectively support critical thinking, contextual reasoning, and independent learning in Office Management courses. In conclusion, the developed digital book is classified as highly feasible for instructional use and holds substantial potential to enhance learning experiences, although further research is recommended to examine its broader effectiveness and long-term impact on student learning outcomes.